ISOLASI, KARAKTERISASI, DAN AMOBILISASI Î±-AMILASE DARI Aspergillus oryzae FNCC 6004 - Jayanti, Dwi (Chem Info Journal, 2013)
Isolation, characterization, and immobilization of Î±-amylase from Aspergillus oryzae FNCC 6004 done to obtain Î±-amylase was isolated from Aspergillus oryzae FNCC 6004 with the highest specific activity, get the data characteristics of Î±-amylase results isolation which include temperature and pH optimum, to get immobilized Î±-amylase, the activity of immobilized Î±- amylase, and reccurence test of immobilized Î±- amylase of Aspergillus oryzae FNCC 6004. Alpha amylase that successfully isolated a specific activity measurements subsequently before immobilization and carried out characterization that includes the determination of the optimum temperature and optimum pH and done immobilization using bacto agar matrix. The specific activity of Î±-amylase before immobilized of 3.26 Unit/mg of protein. The results of the characterization of Î±-amylase shows a optimum temperature of 40 Â°C and optimum pH 4.5. The activity of immobilized Î±-amylase after experiencing a decrease of 17.91 %, it that is from 6.81 Unit became 5.56 Unit with two times reccurence test.